(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Coronary artery perforation, a rare but deadly complication of percutaneous coronary intervention (PCI), can be managed by several modalities, including balloon inflation, heparin-reversing agent, thrombin injection, microcoils, fat embolization, covered-stent implantation, or surgery. We share our experience in emergency innovative management of coronary perforation during routine PCI. We faced an Ellis class III perforation of the right coronary artery during PCI. The balloon inflation technique failed to occlude the perforation, and no other facility was available to solve the problem immediately. The patient developed mild pericardial effusion but was hemodynamically stable. We made a covered stent by wrapping it with polyurethane (Tegaderm® skin dressing material) and deployed it. The perforation was sealed. The patient was discharged in stable condition and doing well at a 12-month follow-up examination. Hand-made covered stent may be a good bailout option to seal coronary perforation where premounted covered stents are not readily available.